Pengaruh Penambahan Grafena Dan Waktu Kalsinasi Terhadap Karakteristik Batu Bata - Puji Rahmawati Dwi Sukma; Amun Amri; Aman Aman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study aims to produce bricks with the addition of few layers graphene (FLG) and to study the effects of graphene addition and calcination time to the characteristics of the bricks produced. The brick-graphene composites synthesis was started from the manufacture of FLG using the turbulence-assisted shear exfoliation (TASE) method. The graphene was then added to the prepared clay, and formed size 5x5x5 cm3 and dried at room temperature for a week. Then the bricks were calcined with variations of 1-5 hours, and the addition of graphene 5-15%wt in furnace at temperature of 800ºC. The mechanical properties of bricks were obtained from compressive strength and porosity tests. With the addition of graphene and the length of time calcination increased the compressive strength and decreases the porosity in bricks. The results showed that the highest compressive strength (6 MPa) was exhibited by sample with the addition of 15% wt graphene and 5 hours calcination time. The lowest porosity (8%) was showed by sample with the addition of 15% wt graphene and 5-hours calcination time. The structure and morphology of graphene were characterized with the fourier transform infrared spectrophotometer (FTIR) and scanning electron microscopy (SEM), while the crystal size of graphene was probed using the diffraction x-ray (X-RD). The XRD test showed the crystal size FLG of 25.5nm, while the SEM results show that graphene was evenly diffused.Keywords : additives, graphene, clay, compressive strength, porosity